2009
DOI: 10.1037/a0016198
|View full text |Cite
|
Sign up to set email alerts
|

Association of the serotonin transporter gene promoter region (5-HTTLPR) polymorphism with biased attention for emotional stimuli.

Abstract: A deletion polymorphism in the serotonin transporter-linked polymorphic region (5-HTTLPR) has been associated with vulnerability to affective disorders, yet the mechanism by which this gene confers vulnerability remains unclear. Two studies examined associations between the 5-HTTLPR polymorphism and attentional bias for emotional stimuli among non-depressed adults. Biased attention, attention engagement, and difficulty with attention disengagement were assessed with a spatial cueing task using emotional stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
134
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 51 publications
(75 reference statements)
15
134
2
1
Order By: Relevance
“…It has been proposed that the short allele variant, associated with a reduced 5-HT function, causes increased brain responses to negative stimuli (Bethea et al, 2004). Beevers, Wells, Ellis, and McGeary (2009) also demontrated that variations in the 5-HT polymorphism are associated with attentional processing of emotional information in a nonclinical population. It was found that short allele carriers show impaired disengagement from emotional material.…”
Section: Neurobiological Underpinnings Of Impaired Attentional Contromentioning
confidence: 99%
“…It has been proposed that the short allele variant, associated with a reduced 5-HT function, causes increased brain responses to negative stimuli (Bethea et al, 2004). Beevers, Wells, Ellis, and McGeary (2009) also demontrated that variations in the 5-HT polymorphism are associated with attentional processing of emotional information in a nonclinical population. It was found that short allele carriers show impaired disengagement from emotional material.…”
Section: Neurobiological Underpinnings Of Impaired Attentional Contromentioning
confidence: 99%
“…Hence, attentional bias for negative information is a hallmark feature of MDD (see Scher et al, 2005), which relates to impaired cognitive inhibition toward negative emotional material (Goeleven et al, 2006;Gotlib et al, 2005;De Raedt and Koster, 2010). In support, 5-HT is implicated in decreased attentional control over negative stimuli by modulating prefrontal-amygdala connectivity (see Cools et al, 2008), and S/S show enhanced emotional amygdala responses (Hariri and Holmes, 2006) and impaired disengagement to emotional information (Beevers et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This means that high scores in this scale for positive emotionality would indicate a heightened responsiveness to emotional stimuli. Specifically, such an increased reactivity for positive as well as negative emotional stimuli has been demonstrated in s-allele-carriers several times (e.g., Canli et al, 2005;Herrmann et al, 2007;Beevers et al, 2009). One could, insofar, speculate that the MPQ more closely depicts emotional responsiveness and reflects its biological underpinnings more adequately.…”
Section: Discussionmentioning
confidence: 98%
“…Alongside an altered attention to unpleasant stimuli (Pergamin-Hight et al, 2012), some studies demonstrated that s-allele-carriers, unlike ll-homzygotes, also selectively attend to pleasant stimuli (Beevers et al, 2009(Beevers et al, , 2011Fox et al, 2011). Neuroimaging studies underpin this association, showing heightened neuronal activation in response to negatively- (Munafo et al, 2008) as well as positively-valenced stimuli in s-allele-carriers (Canli et al, 2005;Herrmann et al, 2007;Klucken et al, 2012).…”
Section: Introductionmentioning
confidence: 99%